Cerebral oxidative metabolism is decreased with extreme apnoea in humans; impact of hypercapnia. (9th July 2016) - Bain, Anthony R.; Ainslie, Philip N.; Hoiland, Ryan L.; Barak, Otto F.; Cavar, Marija; Drvis, Ivan; Stembridge, Mike; MacLeod, Douglas M.; Bailey, Damian M.; Dujic, Zeljko; MacLeod, David B.
Abstract : Key points: The present study describes the cerebral oxidative and non‐oxidative metabolism in man during a prolonged apnoea (ranging from 3 min 36 s to 7 min 26 s) that generates extremely low levels of blood oxygen and high levels of carbon dioxide. The cerebral oxidative metabolism, measured from the product of cerebral blood flow and the radial artery‐jugular venous oxygen content difference, was reduced by ∼29% at the termination of apnoea, although there was no change in the non‐oxidative metabolism. A subset study with mild and severe hypercapnic breathing at the same level of hypoxia suggests that hypercapnia can partly explain the cerebral metabolic reduction near the apnoea breakpoint. A hypercapnia‐induced oxygen‐conserving response may protect the brain against severe oxygen deprivation associated with prolonged apnoea. Abstract: Prolonged apnoea in humans is reflected in progressive hypoxaemia and hypercapnia. In the present study, we explore the cerebral metabolic responses under extreme hypoxia and hypercapnia associated with prolonged apnoea. We hypothesized that the cerebral metabolic rate for oxygen (CMRO2 ) will be reduced near the termination of apnoea, attributed in part to the hypercapnia. Fourteen elite apnoea‐divers performed a maximal apnoea (range 3 min 36 s to 7 min 26 s) under dry laboratory conditions. In a subset study with the same divers, the impact of hypercapnia on cerebral metabolism was determined using varying levels of hypercapnic breathing, against the background of similar hypoxia. In both studies, the CMRO2 was calculated from the product of cerebral blood flow (ultrasound) and the radial artery‐internal jugular venous oxygen content difference. Non‐oxidative cerebral metabolism was calculated from the ratio of oxygen and carbohydrate (lactate and glucose) metabolism. The CMRO2  was reduced by ∼29% ( P  < 0.01, Cohen's d  = 1.18) near the termination of apnoea compared to baseline, although non‐oxidative metabolism remained unaltered. In the subset study, in similar backgrounds of hypoxia (arterial O2 tension: ∼38.4 mmHg), severe hypercapnia (arterial CO2 tension: ∼58.7 mmHg), but not mild‐hypercapnia (arterial CO2 tension: ∼46.3 mmHg), depressed the CMRO2 (∼17%, P  = 0.04, Cohen's d  = 0.87). Similarly to the apnoea, there was no change in the non‐oxidative metabolism. These data indicate that hypercapnia can partly explain the reduction in CMRO2 near the apnoea breakpoint. This hypercapnic‐induced oxygen conservation may protect the brain against severe hypoxaemia associated with prolonged apnoea. Key points: The present study describes the cerebral oxidative and non‐oxidative metabolism in man during a prolonged apnoea (ranging from 3 min 36 s to 7 min 26 s) that generates extremely low levels of blood oxygen and high levels of carbon dioxide. The cerebral oxidative metabolism, measured from the product of cerebral blood flow and the radial artery‐jugular venous oxygen content difference, was reduced by ∼29% at the termination of apnoea, although there was no change in the non‐oxidative metabolism. A subset study with mild and severe hypercapnic breathing at the same level of hypoxia suggests that hypercapnia can partly explain the cerebral metabolic reduction near the apnoea breakpoint. A hypercapnia‐induced oxygen‐conserving response may protect the brain against severe oxygen deprivation associated with prolonged apnoea.